2021
DOI: 10.3389/fmed.2021.795984
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Tophi and Inflammation Are Associated With Carotid Atheroma Plaques in Gout

Abstract: Objective: Gout and cardiovascular disease are closely related, but the mechanism connecting them remains unknown. This study aims to explore whether urate crystal deposits and inflammation (assessed by ultrasound) are associated with carotid atherosclerosis.Methods: We included consecutive patients with crystal-proven gout newly presenting to a tertiary rheumatology unit. Patients under urate-lowering treatment were excluded. Ultrasound assessment was performed during intercritical periods. Musculoskeletal sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 47 publications
0
14
1
Order By: Relevance
“…Tophaceous gout is recognized as a leading cardiovascular predictor, 29,33 and patients with oligoarticular or polyarticular presentation, higher SU levels, and longer disease duration also suffer from CVEs more frequently 29,34 . Although our results could not confirm this impact in a population with cardiovascular disease—probably due to the small number and varying disease stages of included patients—these associations are indicative of the negative impact of large MSU crystal burdens and their subsequent persistent inflammation, as recently confirmed by data using dual-energy computed tomography 35 and ultrasound 36 . Serum urate normalization leads to crystal depletion, so European League Against Rheumatism experts recommend prompt ULT for patients with larger crystal burden and/or established cardiovascular disease 37 .…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Tophaceous gout is recognized as a leading cardiovascular predictor, 29,33 and patients with oligoarticular or polyarticular presentation, higher SU levels, and longer disease duration also suffer from CVEs more frequently 29,34 . Although our results could not confirm this impact in a population with cardiovascular disease—probably due to the small number and varying disease stages of included patients—these associations are indicative of the negative impact of large MSU crystal burdens and their subsequent persistent inflammation, as recently confirmed by data using dual-energy computed tomography 35 and ultrasound 36 . Serum urate normalization leads to crystal depletion, so European League Against Rheumatism experts recommend prompt ULT for patients with larger crystal burden and/or established cardiovascular disease 37 .…”
Section: Discussioncontrasting
confidence: 51%
“…29,34 Although our results could not confirm this impact in a population with cardiovascular diseaseprobably due to the small number and varying disease stages of included patients-these associations are indicative of the negative impact of large MSU crystal burdens and their subsequent persistent inflammation, as recently confirmed by data using dual-energy computed tomography 35 and ultrasound. 36 Serum urate normalization leads to crystal depletion, so European League Against Rheumatism experts recommend prompt ULT for patients with larger crystal burden and/or established cardiovascular disease. 37 As lower SU levels are associated with faster tophi disap-pearance and effective crystal dissolution, it is likely that these patients would also benefit from rigid SU targets.…”
Section: Discussionmentioning
confidence: 99%
“…1 Evidence describes associations between gout and cardiovascular disease. [2][3][4] High urate levels and presence of subcutaneous tophi have both been associated with an increased risk of mortality in patients with gout, and it was suggested that total body urate load could be a plausible pathophysiological link between gout and cardiovascular disease. 5 The volume of crystal deposition measured with dual-energy CT (DECT) has been found to be a biomarker for the risk of developing new cardiometabolic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Gout is caused by deposition of monosodium urate (MSU) crystals in joints and/or extra-articular tissues and gout has increased in incidence the last decades 1. Evidence describes associations between gout and cardiovascular disease 2–4. High urate levels and presence of subcutaneous tophi have both been associated with an increased risk of mortality in patients with gout, and it was suggested that total body urate load could be a plausible pathophysiological link between gout and cardiovascular disease 5.…”
Section: Introductionmentioning
confidence: 99%
“…A prospective 5-year follow-up study confirmed that the presence of carotid plaques predicted the development of cardiovascular events and death in patients with RA ( 39 ). A recent study showed that the presence of tophi and a positive power Doppler signal were significantly associated with atheroma plaques in 103 Spanish gout patients ( 40 ). Also, the increased IMT measurement showed no association with MSU crystal, which is similar to our study.…”
Section: Discussionmentioning
confidence: 99%